PENINGKATAN HASIL BELAJAR SENI MUSIK MELALUI STRATEGI PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH DI SMP - Afdison, Yuvensius (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research aimed to describe the application and student learning achievement in music subject by using â€œmake a matchâ€ cooperative learning strategy in VII B grade Bruder Singkawang junior high school. The background for this research is amount of students that failed to reach standard school grades of music subject in VII B grade class where have more failed student compare with other VII grade classes. This research using descriptive method, with action research form, participation action research type and nature of research is collaborative. Data collection techniques used are observation, measurement, and documentary study. This research conducted for 2 cycles with 2 meeting each cyle. Data analysis used in this research is data tabulation of student learning achievement. Based research result with application of â€œmake a matchâ€ cooperative learning, the student showing the principle of cooperative learning like positive interdependence, responsibility behaviour, interaction and discussion, communicate each other and active in learning activities. With research successful indicator student achieve > 75 school grades, in cyle I, 31 student (91,1%), reach minimum standard and in cyle II increase again to 33 student (97,1%). Keyword: learning achievement, music subject, learning strategy, cooperative, make a match.